Challenges Faced by Caregivers of Individuals With Substance Use Disorder in Pakistan: A Qualitative Study - Anila Sadaf Mubashir; Rida Kainaat; S. M. Yasir Arafat (Health Science Reports)
ABSTRACT Background and Aims Caregivers play a vital role in the treatment of individuals with substance use disorders (SUDs) and encounter numerous challenges. It is essential to highlight these challenges to develop appropriate interventions aimed at supporting caregivers of individuals with SUDs. The present study aimed to explore the challenges faced by caregivers while caring for their family members with SUDs. Methods A qualitative research design was employed, and data were collected through semi‐structured interviews. The sample consisted of 18 caregivers whose family members were admitted and currently undergoing treatment at a rehabilitation facility in Islamabad, Pakistan. These caregivers represented diverse socioeconomic backgrounds, ethnicities, and cities. Results The major themes that emerged from the study included personal challenges, economic challenges, social challenges, legal challenges, and healthcare‐related challenges. Each theme contained multiple sub‐themes, such as psychological factors, personality traits, family dynamics, societal pressures, financial burdens, drug regulation issues, criminal charges, treatment‐related challenges, and interactions with healthcare professionals. Conclusions There appears to be a lack of consideration for caregivers' challenges in Pakistan in SUDs. It is crucial to provide caregivers of individuals with SUDs with evidence‐based and culturally adapted support to address the challenges they face while caring for their loved ones.